Q: What is 7x-11y 3x-1y-4x 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

There are an infinite number of lines that are all parallel to [ y = 3x + 6 ].Here are ten of them to get you started:y = 3x - 1y = 3xy = 3x + 1y = 3x + 2y = 3x + 3y = 3x + 4y = 3x + 5y = 3x + 5.99y = 3x + 6.001y = 3x + 7.etc.

It is an algebraic expression because it does not contain an equality sign.

3x squared - (3x) squared = 0

I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?

√(24x)4/√(3x) = [242x2√(3x)]/3x = 8(24)x√(3x) = 192x√(3x)

Related questions

3x + 3x + 3x = 3* (3x) = 9x

3x^5 If these are 5 of 3x multiplied together the it must be (3x)^5 =3^5 times x^5

3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0

9x2 + 6x + 1 = 9x2 + 3x + 3x + 1 = 3x(3x + 1) + 1(3x + 1) = (3x + 1)(3x + 1) or (3x +1)2

3X^2 + 9X/3X factor out 3X 3X(X + 3)/3X 3X/3X = 1, so... X + 3 is the simplest form here

3X2 - 3X 3X(X - 1) -----------------------factored, so 3X is gfc

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

There are an infinite number of lines that are all parallel to [ y = 3x + 6 ].Here are ten of them to get you started:y = 3x - 1y = 3xy = 3x + 1y = 3x + 2y = 3x + 3y = 3x + 4y = 3x + 5y = 3x + 5.99y = 3x + 6.001y = 3x + 7.etc.

It is an algebraic expression because it does not contain an equality sign.

3x squared - (3x) squared = 0

3x+4y = 17 -3x -3x 4y = -3x+17 Divide each TERM by 4 y = -3x + 17 4 4